Qualidade de folha de Curcuma Longa L. desidratada obtida com diferentes métodos de secagem - Braga, Monick Cristina (2016)
The aim of this study was to evaluate the physical and chemical quality Curcuma Longa L. leaf submitted to three drying methods: hot air drying, freezedrying and microwave drying, as well as the study of kinetic drying methods by convection and microwave. For the kinetic study the leaves were dried by hot air (60 °C) and microwave drying (900W power). Mathematical modeling using various models was performed, as follows: Lewis, Page, Henderson and Pabis, Wang and Singh, and logarithmic models were used to adjust experimental kinetic data. The results showed that the drying time of microwave was 60 times lower than hot air drying. Page model was the best adjusted the drying kinetics data by both methods. The phenol content was higher in the dry leaf (185.42mg/100g-1±0,65) by microwave (p <0.05) than in the hot air dried leaf (183,76 mg/100g-1±0,60), showing phenolic content greater than three times the fresh leaf (54,88mg/100g-1±0,76). It was observed that the drying process does not influence the color variation (ΔE) of the dried leaf. To study the physical and chemical characterization of Curcuma longa L. leaves by studying the chemical composition of the fresh leaf, mineral composition, antinutritional factors and evaluation of the color change of fresh and dry leaf, they were dehydrated by methods microwave, hot air drying and freezedrying. The chemical composition showed appreciable amounts of protein (39,5g (100g) -1 ± 0.91), carbohydrates (44,74g (100g) -1 ± 1.04), total fiber (34,47g (100g) -1 ± 0.98), and soluble fiber (22,65g (100g) -1 ± 0.65), insoluble fiber (11,81g (100g) -1 ± 0.34), ash (13,81g (100g) - 1 ± 1.05), and low in lipids (2,47g (100g) -1 ± 0.12). The mineral composition showed higher amounts of Na, Mg, K, Ca, P, and Mn. Other minerals are Fe and Zn. It was observed low levels of nitrate 0.05 mg / g ± 0.00 (fresh leaf) and 0,46-0,47mg / g (dry leaves) and showed no cyanogenic compounds in its composition. It was observed that the drying process influence on color variation of the dry leaves, increasing the brightness, diminindo the intensity of green color and causing the change in the shade of green to yellowish green. To study the effect of different methods of preservation (hot air drying, in a microwave and freezedrying) the content of bioactive compounds and antioxidant capacity of turmeric leaves, they were dehydrated by drying in an oven (60 ° C) in microwaves (900 W) and lyophilizing (vacuum of 300 mmHg) until equilibrium moisture content (0.030 kgágua.kgsolido dry- 1 ). The content of total phenolics, tannins hydrolysates and condensates and antioxidant activity (DPPH scavenging, reducing and iron chelation) of dried and fresh Curcuma longa leaves were evaluated. The drying methods led to reduction of all the characteristics assessed on a dry basis (2.77 to 73.86%) and antioxidant capacity compared to fresh leaf (67 to 98%). The microwave drying was preservation method studied which produced the best dry leaves, based on the content of bioactive compounds and antioxidant capacity (top being 0.9 to 612% compared to other methods).